AD’TRANS PROGRAMME EDUCATES STUDENTS TO EMBRACE THE ZEST FOR SUSTAINABILITY WITH THE COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – The Ad’Trans 3.0 Programme, which aims to initiate volunteerism activities among the students of Universiti Sains Malaysia (USM) in reaching out to society by utilising the public transport system under Keretapi Tanah Melayu Berhad (KTMB) railway authority, will see 13 USM students ride the train that passes through areas such as Butterworth, Alor Setar, Arau, Padang Besar and Hatyai in Thailand.